Study on the physiochemical and microbial content of drinking water in and around Al-Nasiriyah province - Safa Fadhil; Amani Jasim; Amal Kamel (Journal of the Pakistan Medical Association, 2023)
Objective: To identify microbial contents of water by physical and chemical analyses in different regions in a Middle East country. Methods: The prospective, cross-sectional study was conducted in and around Al-Nassirya province of Iraq from March to July 2021, and comprised drinking water samples taken from water stations in city centre as well as Al-Dawaya, Al-Shatrah and Al-Nasr districts in the outskirts. Analysis included estimation of turbidity, temperatures, potential of hydrogen, total hardness, and estimation of chlorine, calcium and sodium measured in The-Qar university laboratories, Data was analysed using SPSS version 17. T-test was used to compare the mean values. A p-value of Less than or Equal to 0.05 was considered significant. Results: Of the 10 water samples 1(10%) was collected from the city centre, 4(40%) from Al-Dawaya district, 2(20%) from Shatra district and 3(30%) from Al-Nasr district. Significant differences were found in the samples collected from city centre compared to those from the countryside (p<0.29). Turbidity was less (1.7) in samples from the city centre compared to the three countryside water stations. High levels of chlorine (26), concentration of calcium (199) and sodium (479) were moderately high in samples from Al-Nasiriya city. Microbial growth was detected in samples from Al-Nasr and Al-Dawaya districts where Escherichia coli, staphylococcus aureus and cryptosporidiumparrum were detected in some water stations. Conclusion: Countryside water stations showed changes in standard physiochemical normal values and contamination of drinking water with microorganisms. Keywords: Chlorine, Cryptosporidium parvum, Staphylococcus aureus, Cryptosporidiosis, Cryptosporidium, Escherichia coli, Sodium.